The Principal’s Strategy in Managing Teacher Resources to Improve the Quality of Learning at Madrasah Ibtidaiyah - Muhammad Surul; Abdul Goffar (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
The principal of a madrasah plays a strategic role in determining the direction and quality of learning at Madrasah Ibtidaiyah (Islamic elementary schools). Educational quality is not merely determined by infrastructure, but primarily by the quality of teachers as the driving force of learning. This study aims to analyze the strategies used by madrasah principals in managing teacher resources to enhance learning quality. Employing a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation at several MI institutions in Bondowoso Regency. The findings reveal that principals implemented several managerial strategies, including professional development planning, participatory academic supervision, collaborative culture strengthening, and performance-based reward systems. These strategies improved teachers’ motivation, pedagogical competence, and instructional innovation. The study emphasizes that visionary and humanistic leadership is key to building a sustainable culture of quality learning in MI settings.